'A Masterpiece of Camouflage': Modernism and Interwar Australia. Issue 3 (August 2020) - Cooper, Melinda J.
Abstract : Interwar Australia has often been seen as geographically and culturally distant from the centres of modernity, with 1930s Australian literary culture viewed through the tropes of isolation, insularity and quarantine. Through a reading of Eleanor Dark's experimental novel Prelude to Christopher (1934), I contest this idea, arguing that interwar Australia contained its own latent modernisms and modernities, which were often hidden alongside anti-modernist positions and inside other discourses such as cultural nationalism. This essay contributes to recent reinvestigations of the cosmopolitanism/nationalism binary and calls for these categories to be rethought in more interconnected terms. It also examines Dark's modernist and gendered critique of eugenics in light of the larger project of settler colonialism.